Preparation and Characterization of Antimicrobial PVA/ZnO Nanocomposite for Biomaterial Applications (Journal of University of Babylon for Engineering Sciences, 2018)
Control of microbial infections is a highly important issue in hospitals. Antimicrobial polymers are new kinds of antiseptics, which can be used as alternatives to disinfectants in sometimes. Zinc oxide nanoparticles (90 nm) with polyvinyl-alcohol (PVA) generated by melting route. ZnO NPs was modified by dimethyl sulfoxide (DMSO) to get on uniform distribution within the matrix and then reduce agglomeration. The purpose of this study is to determine the antimicrobial activity of PVA ̸ ZnO nanoparticles against Gram-negative bacteria (Pseudomonas aeruginosa; Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus; Staphylococcus epidermidis) and fungi (Candida albicans,). The effects of concentration and particle size on the antibacterial activity of ZnO nanoparticles was studied using minimum inhibitory concentration (MIC) test and the antimicrobial activity of PVA/ZnO nanocomposite was studied using agar well diffusion method. Results showed that the antimicrobial activity of ZnO nanoparticles with PVA increased with decreasing particle size and increasing concentration of ZnO NPs. Results showed that all microbes were fully inhibited at 3.7 μg / ml concentration for ZnO NPs, but activity against bacteria was not observed at 1.8 μm / ml.